Economic crises, high public pension spending and blame-avoidance strategies: Pension policy retrenchments in 14 social-insurance countries, 1981 - 2005 - Juan J. Fernandez (Max Planck Institute for the Study of Societies, 2010)
This paper examines the determinants of the timing of public pension policy retrenchments in 14 affluent democracies. Available research does not satisfactorily capture the multidimensionality of these legislative events, because it relies on indicators of pension policy provisions for current pensioners even though recent retrenchment pension reforms have been characterized by phased-in or grandfathering measures. Instead, this paper identifies these events by considering the individual long-term implications of each pension reform passed in 14 OECD social-insurance countries between 1981 and 2005. Based on a synthetic review of the pension policy literature, data from financial projections, and principles from the economics of welfare programs, I identify 62 pension retrenchments passed in these countries. My argument is that macroeconomic conditions, size of public pension system, and stage in the electoral cycle shape the likelihood of pension retrenchments. Results obtained from conditional frailty models for recurrent and sequential events support this argument. The interval between pension retrenchments is shorter in countries with low economic growth and high public pension spending, as well as in countries in a post-election year. – – Dieses Papier betrachtet die zeitlichen Muster von Rentenkürzungen und deren Determinanten in wohlhabenden Demokratien. Die derzeitige Forschung berücksichtigt die Multidimensionalität dieser legislativen Maßnahmen nur unzureichend, da sie sich auf die Indikatoren für die aktuelle Rentnerpopulation konzentriert, obwohl diese in Zusammenhang mit bereits eingeleiteten oder früheren gesetzlichen Maßnahmen stehen. Die vorliegende Studie hingegen bezieht die Langzeitfolgen der Rentenreformen und deren Entwicklung in vierzehn OECD Ländern im Zeitraum von 1981 bis 2005 in die Analyse ein. Auf der Grundlage einer zusammenfassenden Bestandsaufnahme der Literatur zur Rentenpolitik, von Daten aus finanziellen Hochrechnungen sowie der ökonomischen Prinzipien von Wohlfahrtsprogrammen werden in diesen Ländern zunächst insgesamt 62 Rentenkürzungsmaßnahmen identifiziert. Zur Erklärung der zeitlichen Abfolge der Maßnahmen werden die makroökonomischen Bedingungen, die Größe des Rentensystems sowie die Zeitpunkte der Anpassungen im Wahlzyklus herangezogen. Die unter Anwendung konditionaler Frailty-Modelle erzielten Resultate stützen das Argument, dass die häufigsten Rentenkürzungen sich in Ländern im Jahr nach der Wahl sowie in Ländern mit geringem Wirtschaftswachstum und hohen Rentenausgaben finden.
Keywords: 300